Saving our bacon: changing perceptions of the pig vet. (7th May 2016) - Webster, Grace
Abstract : Over the past few decades, the pig industry and the veterinary role within it has undergone significant change. As part of Veterinary Record's series examining the state of different sectors of the veterinary profession, Grace Webster looks at the challenges facing the pig sector and what the future might hold for the pig veterinarian.